Psychological determinants of commitment and attitudes toward work termination: the effect of locus control on turnover intention - Zayas, Muhittin (My University, 2006)
Bu çalısma, çalısanların is degistirme egilimlerine etki edebilecek etmenleri incelemektedir. Arastırmada sunulan modelde, is degistirme egilimini etkileyen bagımsız degisken olarak kontrol odagı gösterilmis, ‘kontrol odagı algısı - isten ayrılma egilimi’ iliskisini modere edebilecegi varsayımıyla, çalısanın kurumuna karsı hissettigi örgütsel baglılık, alternatif is olanaklarının varlıgı ve bireylerin sık is degistirme davranısına karsı genel tutumu gibi unsurlarla, cinsiyet, yas, kıdem, egitim düzeyi, medeni durum, gibi demografik faktörler de ölçümlenmistir. Benzer çalısmaların sonuçları ve degerlendirmeleri giris bölümünde sunulmustur. Veri havuzunu tamamı ulusal ya da uluslararası büyük sirketlerden, herhangi bir yönetsel fonksiyonu olmayan toplam 170 beyaz yakalı çalısanın olusturdugu çalısmanın istatistiksel sonuçları, kontrol odagı algısının is degistirme egilimi üzerinde anlamlı bir etkiye sahip oldugunu göstermistir. s degistirme egiliminin yas ve medeni durum gibi bazı demografik faktörlerle de anlamlı bir iliskisi oldugu saptanmakla birlikte, kıdem, cinsiyet ve egitim gibi diger degiskenler söz konusu oldugunda aynı iliski gözlenememistir. Öte yandan, yukarıda sözü edilen diger moderatör etmenlerin tamamının is degistirme egilimiyle iliskisi oldugu ortaya çıkmıstır. Degerlendirme bölümünde sonuçlar yorumlanmıs ve konuyla ilgili ilerideki çalısmalar hakkında öneriler sunulmustur.

This study reports on an investigation of factors that may predict intentions of a jobholder’s to leave his or her job, and tests a model that includes moderating factors. In the design of the study, locus of control was attributed a main role in predicting turnover intention, and other factors that may contribute to the decision to quit like, organizational commitment, perceived alternative employment opportunities, general attitudes of individuals towards job-hopping were treated as moderators in the model. A summary of literature survey cited. A total of 170 white-collar employees from national or international large organizations holding a non-managerial position filled in a questionnaire measuring the variables above. Results pointed to a statistically significant relationship between the predictor and the dependent variable: participants with an external locus of control did show a higher turnover intention. While some demographics like age and marital status were shown to play a role in decision of leaving or not, some others like gender, seniority and level o formal education were not. Moreover, turnover intention appeared to be related with organizational commitment (inversely), with job-hopping attitude, and with participants’ perceptions of employment opportunities outside the organization. Evaluation of the results, discussions of the limitations of the study, and projections for further research provided. locus of control, turnover intention
Keywords: Çalışma Hayatı; Kontrol (Psikoloji)